THE TOURISM POTENTIAL OF KE’TE KESU VILLAGE AS A CULTURAL HERITAGE ATTRACTION AND HISTORICA ICON OF TORAJA - Ernawati Ernawati (INJOSEDU: International Journal of Social and Education, 2025)
This research examines the potential of Kete Kesu Village as a tourist attraction and historical icon of Toraja, South Sulawesi. The formulation of the problem studied in this research is what is the potential of Kete Kesu village as a tourist attraction in Toraja. The method used is a qualitative research method with a qualitative descriptive approach to understand what phenomena the research subjects experience. Meanwhile, the data collection techniques in this research are literature study and documentation. The results of this research show that Kete Kesu is one of the interesting tourist villages to visit in Toraja because it has interesting and unique tourism potential and has a history that was considered mystical and romantic in ancient times.